ANALISIS STRATEGI KOMUNIKASI GURU PAI DALAM MENGEDUKASI ORANG TUA TENTANG PARENTING ISLLAMI DI SMP TAQ Al HAMIDIYYAH BATEALIT - Azkal Nufus; Mufid (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2026)
This study analyzes the communication strategies of Islamic Religious Education teachers in Islamic parenting education for parents at SMP TAQ Al Hamidiyyah Batealit. A qualitative case study method was employed with data collection techniques through interviews, observation, and documentation. data reduction, data presentation, and drawing conclusions The results identify four main strategies: group communication (majelis taklim), interpersonal communication (counseling), utilization of digital media, and behavioral exemplification (uswah hasanah). These strategies proved effective in creating school-family synergy and enhancing parental understanding, despite challenges of background heterogeneity. The research concludes by emphasizing the importance of an integrated multi-method approach for successful parenting programs. Recommendations focus on developing structured modules and optimizing more interactive communication channels.